Analisis Keterlibatan Mahasiswa Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar pada Lembaga Kemahasiswaan dan Efektifitasnya dalam Dakwah - Syandri Syandri; Askar Fatahuddin; Ahmad Syaripudin; Agus Miranto; Edwin Salnar Sose (Jurnal Dakwah dan Komunikasi, 2021)
This study aims to analyze the involvement of STIBA students in student organizations and their effectiveness in da'wah as a reference material for policy makers of the Makassar Islamic and Arabic Language College (STIBA) to establish better student regulations for the development of students and alumni of STIBA Makassar. The formulation of the first problem concerns the involvement of STIBA Makassar students in student institutions, the second is the effectiveness of da'wah for STIBA Makassar alumni at the Assignment location, and the third is an analysis of student involvement in LK as well as resilience and creativity in da'wah. This research uses field research with qualitative analysis research methods, namely using in-depth data analysis in the form of numbers. The results of this study indicate that in general STIBA students during the study period have joined the Student Affairs Institute but the involvement tends to decrease from year to year. The effectiveness of the alumni's da'wah while at the job site is measured by militancy, resilience and creativity also needs intense guidance by the relevant sections within the scope of the STIBA institution, while the correlation of student involvement in student institutions to the effectiveness of da'wah has proven to be quite positive even though most of it is only at the institutional level have not been able to do a lot of creative da'wah with other institutions externally.